Case report: specific phobia of vaginal penetration in a pregnant patient - Geng, Wenqi; Cao, Jinya; Jin, Li; Wei, Jing (Frontiers in Psychiatry, 2023)
Specific phobia is frequently unrecognized or untreated unless it causes significant impairment. In this report, we documented a rare case of a pregnant patient who had a specific fear related to vaginal penetration. Due to abnormal fetal cardiac development in the second trimester, the patient was admitted for termination of pregnancy. The patient's persistent request for surgical termination via Csection prompted the obstetrician to seek psychiatric consultation for tokophobia, a labor-and childbirth-related phobia. The consulting psychiatrist discovered that the patient had developed a significant fear of vaginal penetration during adolescence. Throughout the extended period of this specific phobia, the patient established a range of avoidance strategies. Had it not been for the unforeseen need for abortion, her phobia may not have been identified. Psychoeducation on specific phobias, exposure therapy, muscle relaxation techniques, and the administration of anxiolytics were implemented. The pregnancy was terminated through a vaginal labor induction procedure two days This is a provisional file, not the final typeset article later. Collaboration across disciplines is necessary to support a thorough assessment of obstetric patients who express hesitancy towards vaginal delivery.